A Historical and Clinical Perspective Endorsing Person-centered Management of Fibromyalgia Syndrome - T. Masi, Alfonse; Vincent, Ann (Current Rheumatology Reviews, 2015)
Fibromyalgia or fibromyalgia syndrome (FMS) is a complex chronic pain disorder of unknown causation frequently associated with debilitating fatigue, unrefreshing sleep, cognitive and affective symptoms. A fibromyalgia-type suffering was possibly described in the Book of Job. Analogous symptomatic conditions have been medically recognized since the early 1900s, when initially labeled as “fibrositis”. Since the early 1980s, FMS has evolved and differentiated after its characterization in a controlled study. Since then, research has focused on multiple aspects of this disorder, including characterization and management of symptoms, psychophysiology, neuroendocrine-immune pathophysiology, including central sensitization mechanisms. The complex and multifaceted nature of FMS lends itself better to a holistic (integrative medicine) or biopsychosocial approach than the more specific bioscientific pathways typical for a pathologically-defined disease. A person-centered approach to evaluation and care more effectively addresses and encompasses the biopsychosocial aspects of this disorder than traditional bioscientific clinical methods. This review outlines a holistic multi-modal, patientcentered approach to evaluation and care as a framework for primary clinic settings. Future directions in research, diagnosis, and management of fibromyalgia patients should incorporate revised person-centered and other qualitative models of care for critical comparison to current conventional concepts and clinical practice. The more comprehensive personcentered services need to be compared to the current standardized practice in terms of their cost-effective outcomes, patient satisfaction, physician gratification, and practical logistics of providing long-term follow up and management.
Keywords: patient-centered